Palaeoenvironmental and palaeoclimatic inferences based on X-ray computer tomography: a case study of alkaline lake deposits in Hungary - Alzoubi, Nour N.; Gulyas, Sandor; Geiger, Janos (Geologos, 2023)
Widely distributed freshwater carbonate sediments, i.e., limestone, dolomitic limestone and dolomite, developed in inter-dune alkaline ponds of the Danube-Tisza Interfluve in the centre of the Carpathian Basin during the Holocene. The key parameters that determine the formation of any given type of carbonate mineral (calcite, dolomite) are temperature, evaporation rate, pH and ion concentrations, in addition to CO2 absorption by aquatic plants. CT analysis is capable of recording small-scale density variations attributable to compositional differences of sedimentary rocks. As the type and proportion of rock-forming minerals and other components is an artifact of past environmental and climatic conditions, CT values may act as potential palaeoenvironmental proxies. The present study compares variations in rock-forming components obtained for freshwater carbonates utilizing the CT method with already available geochemical and palaeoecological proxy data. Variations in molluscan ecology and isotope geochemistry, sedimentation times and CTbased rock density values all indicate the relevance of millennial-scale, climate-driven changes in carbonate formation. As previously observed, the emergence of colder conditions in the North Atlantic, which resulted in increased cyclonic activity and heavier rainfall in western Europe and the Danube watershed area between 10.3 and 9.3 kyr cal BP, resulted in the emergence of humid conditions favouring a rise in the groundwater table at our site and precipitation of calcite from pore waters as opposed to high-magnesium calcite. This is clearly reflected in a negative shift in CT density values in our dated rock samples.